Adipose-Derived Stem Cells Promote Proliferation, Migration, and Tube Formation of Lymphatic Endothelial Cells In Vitro by Secreting Lymphangiogenic Factors. Issue 6 (June 2015) - Takeda, Kohsuke; Sowa, Yoshihiro; Nishino, Kenichi; Itoh, Kyoko; Fushiki, Shinji
<x xml:space="preserve">Abstract</x> Abstract Adipose-derived stem cells (ADSCs) are a promising new therapeutic modality for several diseases and have been applied to various clinical fields because of their multidifferentiation potential and capacity for growth-factor secretion. Recently, 2 in vivo studies showed ADSCs to have potential applications in lymphedema therapy. However, it remains unclear whether ADSCs have direct effects on lymphatic endothelial cells (LECs). In this study, human LECs were treated with murine ADSC-derived conditioned media. Changes in LEC proliferation, migration, and tube formation were assessed by WST-8 assay, transwell chamber assay, and Matrigel-based tube formation assay, respectively, with recombinant human vascular endothelial growth factor-C used as a positive control. Additionally, the expression of several lymphangiogenic factors in ADSCs was examined by quantitative reverse transcription-polymerase chain reaction and enzyme-linked immunosorbent assay. Factors secreted by ADSCs induced LEC proliferation, migration, and tube formation more potently than recombinant human vascular endothelial growth factor-C. We confirmed by quantitative reverse transcription-polymerase chain reaction and enzyme-linked immunosorbent assay that some of the lymphangiogenic factors of ADSCs were dramatically up-regulated under serum-starved conditions. These data indicate that ADSCs could directly contribute to lymphangiogenesis via secretory factors in vitro and may thus provide a therapeutic modality for patients with lymphedema.